The dual nature of escapism in video gaming: A meta-analytic approach - Umer Hussain (Elsevier, 2021)
Researchers have previously argued that escapism via video games can lead to negative and positive outcomes. The purpose of this study was to investigate which outcomes (negative or positive) outweigh the others. Further, the authors examined how the cultural context (Western and Non-Western) affects the association between escapism and its dual outcomes. To achieve the study aims, the authors conducted two meta-analyses using the PRISMA approach. The authors included 27 studies having a sample size of N ​= ​28,893 in the two meta-analyses. The results show that escapism has a significant relationship with both negative (Q (40) ​= ​2411.001, p ​< ​.001) and positive outcomes (Q (67) ​= ​6384.554, p ​< ​.001). However, negative outcomes (ZRE ​= ​0.46) outweigh the positive outcomes (ZRE ​= ​0.34). Further, the results highlight that cultural context (Western and Non-Western) significantly moderates the relationship between escapism and its dual outcomes. The authors discuss the theoretical implications and limitations of the study.